Developmental connections between cranial components and the emergence of the first permanent molar in humans - Sardi, Marina Laura (2007)
The age of emergence of the first molar (M1) is a developmental event correlated with many variables of primate life history, such as adult brain size. The evolution of human life history is characterized by the inclusion of childhood, which takes place between weaning and M1 emergence. Children still depend on adults for nutrition due to their small digestive system and their immature brains. By contrast, juveniles are not dependent because of M1 emergence, which enables shifting to adult type diet, and attainment of nearly adult brain size. In this study, developmental connections between M1 emergence and growth of cranial components were explored in two ways in order to understand the developmental basis of their evolutionary connections: (1) differences in growth trajectories of cranial components with respect to M1 emergence and (2) differences between individuals with and without fully emerged M1. Growth of anteroneural, midneural, posteroneural, otic, optic, respiratory, masticatory and alveolar cranial components was analysed in human skulls of individuals aged 0-20 years and in an adult reference skull. Volumetric indices were calculated to estimate size. Two subsamples were selected in order to focus on the transition between deciduous and permanent dentition: those with full deciduous dentition and before M1 reaches the occlusal plane; and those who present M1 in full emergence and no other cheek-tooth at the occlusal plane. The principal results were as follows. (1) Trajectories fitted using the whole sample are characterized by an inflection point that takes place before M1 emergence for neural components and around M1 emergence for facial components. (2) Associations between growth and age tend to be strong in those with full deciduous dentition, and weak in those who present M1 in full emergence. (3) Individuals who present M1 in full emergence are larger than those with full deciduous dentition. (4) Growth of components linked to the central nervous system is not linear until M1 emergence. Individuals who present M1 in full emergence are only larger than individuals with full deciduous dentition by 4-5% of adult size. (5) The alveolar component does not show increments between full deciduous dentition and M1 emergence. (6) When volumetric indices were standardized by age, the growth trajectories of individuals with full deciduous dentition and of those with M1 were not decoupled. In general terms, M1 emergence does not show a strong association with growth of the components that may explain differences in life histories. However, the main changes in neural and alveolar components occur in the first 3 years of life, which may be developmentally connected with M1 crown formation.